Optimizing NPSB fertilizer rates for enhanced yield and yield components of mung bean (Vigna radiata L:) varieties - Daniel Manore; Hiwot Kelbo; Oumer Abdella; Francis Abuye (PLoS ONE, 2025)
Ethiopia’s mung bean sector faces profound constraints: persistently degraded soils, critically low adoption of essential NPSB fertilizers, and a severe shortage of improved varieties. These factors collectively cripple the crop’s inherent productivity and national potential. To directly address these barriers, this two-year field study (2022 and 2023) evaluated the synergistic effects of improved mung bean varieties and NPSB fertilizer application on crop performance. The experiment was conducted using a factorial design within a randomized complete block layout, replicated 3 times, to test 3 key varieties: NVL-1, N-26, and Arkebe, at 5 different NPSB fertilizer rates of 0, 25, 50, 75, and 100 kg per hectare. Results decisively demonstrated that optimal growth and yield parameters were consistently achieved at the highest fertilizer levels (75 and 100 kg ha ⁻ ¹). The N-26 variety emerged as the best across critical metrics, including plant height, branching, seed yield, and harvest index throughout both years. A standout performance occurred in 2022, where N-26 combined with 100 kg ha ⁻ ¹ NPSB produced a peak grain yield of 1.94 t/ha. Arkebe’s best yield was 1.78 t/ha at 75 kg ha ⁻ ¹, higher than other varieties. Economic analysis further solidified N-26’s superiority: paired with 100 kg ha ⁻ ¹ NPSB, it delivered the highest net benefits, 47,704.17 ETB per hectare in 2022 and 49,856.85 ETB per hectare in 2023. Therefore, applying NPSB fertilizer at 100 kg ha ⁻ ¹ to the N-26 variety is recommended to maximize mung bean productivity and profitability in the studied context.